Pathogens constancy, harbinger of nosocomial infection cum identification of resistant genes and drug designing. (June 2018) - Ahmad, Sana Farooq; Khan, Ibrar; Wadood, Abdul; Azam, Sadiq; Rehman, Noor; Waqas, Muhammad; Bashir, Kashif; Khan, Asaf Ali
Graphical abstract: Highlights: Hospitals are the most prominent places for the growth and spread of bacteria which are resistant to the available antibiotics. Samples were collected from 1010 inanimate objects of gynecology, Operation Theater (OT), medicine and dental ward, inoculated and incubated. For Antibiotic sensitivity disc diffusion method was used and ESBL and MBL isolates were identified. Antibiotic resistant genes blaTEM, AmpC, CTX-M and NDM-1 were screened and amplified. In-Silico Approach was used for β-lactamase TEM, Metallo-β-lactamase and β-lactamase proteins to find new and potent inhibitors. Abstract: Hospitals are the most prominent places for the growth and spread of bacteria which are resistant to the available antibiotics. This antibiotic resistance is due to the over and misuse of antibiotic dosages of a high-density of patient population which are in frequent interaction with inanimate items of the hospitals and the consequent risk of cross infection. Out of 1010 samples of the current study, 510 (50.49%) were culture positive of which 329 (64.5%) were Gram-positive while 181 (35.49%) Gram negative. The Gram positive bacterial isolates in the current study were; S. aureus and S. epidermidis while Gram negative were; Citrobacter, P. aeruginosa, Provedencia, E. coli, Proteus, Klebsiella, Shigella and Serratia . In the current study, 50 ESBL and 10 MBL producing isolates were obtained from inanimate objects. The ESBL positive isolates were highly resistant to MEM. Out of 50 ESBL, 2 isolates were resistant to DO, SXT and FEP while 1 was resistant to TZP and CN. The BlaTEM gene was detected in 22 and BlaCTX was detected in 19 ESBL producing isolates. Six of the MBL producing isolates were NDM positive while all of the isolates were AmpC negative. Most of the isolates had more than two resistant genes. Several classes of inhibitors have been reported for β-lactamase TEM, Metallo-β-lactamase and β-lactamase proteins. Complex-base pharmacophore models were generated on the bases of co-crystalline ligands attached in the 3-D structures of the proteins. The validated pharmacophore models were used for the screening of ZINC drug like database. As a screening results 571 structurally diverse hits of Ethyl Boronic Acid, 866 on L-Captopril and 1020 of Nacubactam were mapped and filtered via Lipinski's rule of five. In conclusion, 30 hits (10 to each protein) having diverse structure and binding modes with all the three proteins active sites were selected as leading novel inhibitors. These selected novel inhibitors have different scaffolds and a strong possibility to act as an additional starting opinion in the development of new and potential inhibitors.